The relationship between teamwork and the workload of nurses with missed nursing care in intensive care units in Iran: a cross-sectional study - Ali Safdari; Fahimeh Ramezani; Erfan Ayubi; Efat Sadeghian (BMC Health Services Research)
Abstract Background Missed nursing care (MNC) is a major challenge faced by nurses working in intensive care units (ICU). Workplace characteristics, including teamwork and workload, can affect the extent of missed nursing care. Examining the relationship between these variables can help create strategies to enhance care. Thus, this study aimed to explore the connection between teamwork, workload, and missed nursing care in the intensive care units of hospitals in Iran. Methods This descriptive cross-sectional study was conducted from August to November 2023 on 219 nurses working in the intensive care units of teaching hospitals affiliated with Hamadan University of Medical Sciences. Participants were selected through multi-stage sampling after meeting the inclusion criteria. Data were collected using the General Characteristics questionnaire, the Team-STEPPS® Teamwork Perception Questionnaire (T-TPQ), the National Aeronautics and Space Administration Task Load Index (NASA-TLX), and the MISSCARE survey. Data analysis was performed using Stata software version 14. Results Out of 219 returned questionnaires (92.79% response rate), 194 valid responses were analyzed. Missed nursing care showed a significant negative correlation with overall teamwork (r = -0.538, P < 0.001) and its subcomponents, including team structure (r = -0.472), leadership (r = -0.303), situation assessment (r = -0.486), mutual support (r = -0.325), and communications (r = -0.517). Tenure was also significantly related to missed nursing care (p = 0.040), with nurses having less than 2 years of experience reporting the lowest missed care scores. No significant relationships were found between workload scores and demographic variables. Conclusion The relationship between teamwork, nurse workload, and missed nursing care is complex. The findings of this study emphasize the importance of effective teamwork and manageable workloads in reducing missed nursing care. However, contextual differences in nurses’ work environments are of great importance in different countries.